2018
DOI: 10.3389/fimmu.2018.02332
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal T Cell Frequencies, Including Cytomegalovirus-Associated Expansions, Distinguish Seroconverted Subjects at Risk for Type 1 Diabetes

Abstract: We analyzed T cell subsets from cryopreserved PBMC obtained from the TrialNet Pathway to Prevention archives. We compared subjects who had previously seroconverted for one or more autoantibodies with non-seroconverted, autoantibody negative individuals. We observed a reduced frequency of MAIT cells among seroconverted subjects. Seroconverted subjects also possessed decreased frequencies of CCR4-expressing CD4 T cells, including a regulatory-like subset. Interestingly, we found an elevation of CD57+, CD28–, CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…7 Peripheral blood MAIT cell alterations during the progression of type 1 diabetes (T1D). Alterations observed in our study in the paediatric cohort (a) and adult cohort (b) are displayed above the black line and those reported in previous studies [34][35][36] are listed below the black line. E, established (more than 10 days after diagnosis); ND, newly diagnosed (less than 10 days after diagnosis); NP, non-progressor; P, progressor Of the MAIT cell alterations observed here, decreased expression of CD27 and production of IFN-γ have also been reported by others in patients with type 1 diabetes [34,35] ( Fig.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…7 Peripheral blood MAIT cell alterations during the progression of type 1 diabetes (T1D). Alterations observed in our study in the paediatric cohort (a) and adult cohort (b) are displayed above the black line and those reported in previous studies [34][35][36] are listed below the black line. E, established (more than 10 days after diagnosis); ND, newly diagnosed (less than 10 days after diagnosis); NP, non-progressor; P, progressor Of the MAIT cell alterations observed here, decreased expression of CD27 and production of IFN-γ have also been reported by others in patients with type 1 diabetes [34,35] ( Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Also, the study by Harms et al did not detect differences in the frequency of 'MAIT-like' cells in children with type 1 diabetes [34]. A more recent study by the same group reported a decreased MAIT cell frequency in AAb + at-risk individuals, especially in those who did not progress to type 1 diabetes [36], which contrasts with our finding of a decreased frequency of MAIT cells in AAb + at-risk children who progressed to type 1 diabetes. Differences in gating strategy for MAIT cells [34], as well as how stringently the study cohorts have been matched for age and HLA background, may explain some of these discrepancies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Studies have indicated that proinflammatory cells such as Th1, Th17, and CTL, which increase in obesity and diabetes, also modulate insulin signaling (3,6). Conversely, a number of antiinflammatory cells, such as Th2 and regulatory T cell (Treg), have been associated with the protection of insulin sensitivity (7).…”
mentioning
confidence: 99%